Multiple Aspirational Contestation of Islamic Mass Organization in Indonesia: A Study of Local Muhammadiyah in Metropolitan Jakarta’s Buffer City - Asep Suryana (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
Despite its peripheral position amid the rapid growth of Depok, a buffer city of Jakarta, an Islamic organization, Muhammadiyah, can still develop and contest both at the grassroots and social-urban levels. This article employs a multiple aspirational contestation framework to analyze Muhammadiyah in Depok as a case study. The research utilizes qualitative methodology through in-depth interviews and observations involving the organization’s members and administrators. The research findings demonstrate that Muhammadiyah in Depok can be categorized as either native- or migrant-patterned. The organizational structure of the movement is characterized by its grassroots level, the establishment of trans-local networks, and a vertical structure consisting of branches (organizing Muhammadiyah at the sub-district level) and regions (organizing Muhammadiyah at the city level). Consequently, Muhammadiyah has the capacity to organize itself within the locality and advocate for the socio-religious aspirations it upholds within the context of the dynamic urban-social milieu. The organization at such a local level also shows collective resilience and capacity to grow in the dynamic buffer city of Jakarta.